Análisis del agua de consumo humano para la elaboración de un sistema de tratamiento, en la hostería reventador, parroquia reventador, cantón Gonzalo Pizarro provincia de Sucumbíos, período 2013-2014 - Alvarado Alulema, Robert Emeregildo (2014)
The water is the liquid most important and abundant in the earthmoreover this is ideal for livesubsistence o. The hydrological cycle determines the physical state of water; this liquid is found in the rain, river, ocean, and solid in the snow, snow, and as gas clouds. The quality of this resource depends on natural factors and human action. The use water in different activities, causes physical altered, chemical, bacteriological and biological characteristics altered, severely affecting the life existence in aquatic ecosystems and all living beings. The present investigation is aimed at performing by physical, chemical and biological analysis of water in the HosteríaReventador piped water distribution systemto diagnose problems that will be present at the end giving technical management criteria....